Prevalence of household food insecurity among a healthy Iranian population: A systematic review and meta-analysis - Arzhang, Pishva; Abbasi, S. Haniye; Sarsangi, Peyman; Malekahmadi, Mahsa; Nikbaf-Shandiz, Mahlagha; Bellissimo, Nick; Azadbakht, Leila (Frontiers in Nutrition, 2022)
Abstract Background: Food security is a fundamental human right that must be upheld to preserve excellent general welfare, and mental, physical and social health. However, according to the United Nation’s Food and Agriculture Organization (FAO) report in 2020, the level of food insecurity in the world is increasing. Objective: Determining the prevalence of food insecurity in Iran will be beneficial for Iran and other low-middle income countries. Methods: We searched both English and Persian (Iranian) databases including PubMed, Scopus, Web of Science, Google Scholar, SID, Irandoc, Magiran, Civilica and Iranian Medical Sciences Theses System from 01 January 1990 to 01 February 2022. Observational studies that reported the prevalence of household food insecurity amongst a healthy Iranian population and assessed food insecurity at the individual or household level using validated questionnaires were included. Results: 106 studies and/or theses with a total of 152, 300 participants met the review criteria. Our analyses demonstrated that the prevalence of food insecurity amongst the healthy Iranian population was 55.9% (95% CI: 52.6% to 59.2%) and the highest prevalence of food insecurity was in the western regions with 64.8% (95% CI: 57.7% to 72.0%). Subgroup analyses showed that food insecurity among women at 51.3% (95% CI: 45.1% to 57.6%) and rural inhabitants at 66.1% (95% CI: 58.8% to 73.4%) was significantly higher than men at 47.8% (95% CI: 41.8% to 53.8%) and urban residents at 47.1% (95% CI: 44.1% to 50.0%), respectively. Among the age groups, the highest prevalence of food insecurity was in adults at 56.5% (95% CI: 51.7% to 61.2%). Conclusions: The prevalence of food insecurity in a healthy Iranian population was higher than the global average. Women, rural residents, and residents of the western regions of Iran had a higher prevalence of food insecurity. These groups should be prioritized in programs to reduce the prevalence of food insecurity in Iran.